Be the best at what matters most the only strategy you will ever need - Calloway, Joe (Gildan Audio, 2020)
Be the Best at What Matters Most is about simplifying how you think and go about your business. Most businesses of today are more focused on the newest gimmicks and tricks of the trade that they believe can save the day. This book focuses on the view that success is a result of quality, consistency of performance, and relentless improvement on those things that matter most and not about the wow factor provided by flashy tricks. It will teach companies to be so good at the basics that they are cutting edge. Questions, activities, and action steps will be built into every section of the book. '